2020
DOI: 10.1101/2020.07.21.213512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A spatially resolved single cell atlas of human gastrulation

Abstract: Gastrulation is the fundamental process during the embryogenesis of all multicellular animals through which the basic body plan is first laid down. It is pivotal in generating cellular diversity coordinated with spatial patterning. Gastrulation in humans occurs in the third week following fertilization. Our understanding of this process in humans is extremely limited, and based almost entirely on experimental models. Here, we characterize in a spatially resolved manner the single cell transcriptional profile o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 71 publications
3
79
0
Order By: Relevance
“…A recent study shows that both genes may be dispensable for hPGCLC specification ( Hancock et al., 2020 ); however, further work is needed to establish the role of these naive pluripotency genes in germline development. Similarly, PRDM14 , which is not detected in CS7 hPGCs ( Tyser et al., 2020 ), is only detectable in some gonadal pPGCs, suggesting that it may not have an essential role during pPGC specification ( Figures 1 B and 1F; Kobayashi et al., 2017 ). Recent evidence shows that PRDM14 may have a role in maintenance of hPGCs after specification ( Sybirna et al., 2020 ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent study shows that both genes may be dispensable for hPGCLC specification ( Hancock et al., 2020 ); however, further work is needed to establish the role of these naive pluripotency genes in germline development. Similarly, PRDM14 , which is not detected in CS7 hPGCs ( Tyser et al., 2020 ), is only detectable in some gonadal pPGCs, suggesting that it may not have an essential role during pPGC specification ( Figures 1 B and 1F; Kobayashi et al., 2017 ). Recent evidence shows that PRDM14 may have a role in maintenance of hPGCs after specification ( Sybirna et al., 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have shown that, after their induction in posterior early-PS Epis, the PGC cluster localizes at the embryonic and extraembryonic border in pig pre-somatic-stage embryos ( Kobayashi et al., 2017 ; Wolf et al., 2011 ). Similarly, in a gastrulating CS7 human embryos, hPGCs have been suggested to emerge from the PS and are set apart from nascent mesoderm and other lineages ( Tyser et al., 2020 ). Importantly, these cell types are induced by BMP signaling, which is detected in the posterior end of the pig embryo from E12 onward ( Valdez Magaña et al., 2014 ; Yoshida et al., 2016 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations